That is an equation.
Oh, you wanted to know for which values of x that equation is true? Okay...
6x + 3x + 8 = 35
⇔ (6x + 3x) + 8 = 35
⇔ 9x + 8 = 35
⇔ 9x + 8 - 8 = 35 - 8
⇔ 9x + 0 = 27
⇔ 9x = 27
⇔ 9x / 9 = 27 / 9
⇔ x = 27 / 9
⇔ x = 3
6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...
3x + 5 = 6x + 23 -3x = 18 x = -6
2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41
x=10
3x+42=6x+12 42=6x-3x+12 42=3x+12 42-12=3x 30=3x 10=x
9x+6 = 6x+15 9x-6x = 15-6 3x = 9 x = 3
6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...
3x + 5 = 6x + 23 -3x = 18 x = -6
x=10
2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41
3x+42=6x+12 42=6x-3x+12 42=3x+12 42-12=3x 30=3x 10=x
3x+50=6x+14 50-14=6x-3x 36=3x x=36 / 3 therefore x=12
the answer is -3x = 0
3x + 7 = 6x - 2 Rearranging gives 6x - 3x = 7 + 2 3x = 9 x = 3
6x+5=3x+5 5=9x+5 x=0
3x(2x + 1)
x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0